Biodiversity Status and its Management at Ramsagar National Park at Dinajpur in Bangladeh - Rimi, RH; Rahman, F; Latif, MB (Journal of Environmental Science and Natural Resources, 2015)
According to this study a heterogeneous species assemblage of 393 species including 272 plants, 24 waterfowl and birds, 14 miscellaneous fauna and 84 species of fish was found at Ramsagar National Park. Among the entire plant types weed was found to be most abundant (36.76%), followed by the medicinal plants 27.57%, ornamental plants 15.07%, timber plant species 10.29%, fruit plants 8.46%, aquatic plants 6.62%, cultivated crops 6.25%, fodder plant 2.21%, spice plants 2.21%, and palm tree 1.84%. All kinds of plants were very common in the study area. In case of fishes, 13.10% was cultivated and 63.10% was small indigenous but 23.81% of small indigenous fishes were threatened. At the study area, 9 species of bank birds (37.50%), 4 species of prey birds (16.67%), and 11 species of waterfowl (45.83%) were found. Among the bank birds, 3 were very common and 4 were few. Among the 4 prey birds 3 species were very few and 1 species was few. In case of waterfowls, 5 species were few, 4 were common, and 1 species was very few. Seven species of miscellaneous faunal species were common, 1 very common, 3 few, and 3 were threatened. Contribution of biodiversity to the local people was mainly for food, although they used plants for furniture, fuel wood, wood, medicine, domestication etc. There was no management plan in the RNP but they had an annual work plan. Only 8 staffs were found for maintaining the Park which could not be adequate for proper management. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22035 J. Environ. Sci. & Natural Resources, 6(1): 21-32 2013